Syphilis and borreliosis during pregnancy - Hercogova, J; Vanousova, D (Dermatologic therapy, 2008)
Syphilis and lyme borreliosis have similar etiologic, clinical, and epidemiologic characteristics. Both are multisystem infectious disorders spread worldwide. Their clinical course can be divided into three stages and as to spirochetal origin, antibiotic therapy is similar too. Taxonomical relationship of Treponema and Borrelia could explain also congenital manifestations well-known in syphilis, and suggested in borreliosis. Therapy of pregnant women with syphilis and lyme borreliosis should follow the same strategy.
Keywords: vrozená syfilis; vertikální přenos infekce; Pregnancy Complications, Infectious; novorozenec; Infant, Newborn; Syphilis, Congenital; Pregnancy; Humans; syfilis; Lyme Disease; lymeská nemoc; Female; dospělí; infekční komplikace v těhotenství; Infectious Disease Transmission, Vertical; lidé; antibakteriální látky; Penicillin G; předškolní dítě; Adult; Congenital Abnormalities; ženské pohlaví; vrozené vady; Anti-Bacterial Agents; penicilin G; těhotenství; Syphilis; Child, Preschool